Between progress and obstacles in urban climate interdisciplinary studies and knowledge transfer to society. Issue 1 (29th November 2018) - Hidalgo, Julia; Lemonsu, Aude; Masson, Valéry
Abstract: Cities modify their local climate, and at the same time they suffer from the local impacts of climate change. Our paper discusses the progress and obstacles in three active research topics that contribute to increasing the capability within the urban climate research community for transferring local climate knowledge to society. The first is linked to the production of urban surface descriptions useful for urban climate studies. The concept of local climate zones is now widely used to represent urban climate variability at the neighborhood scale. Land‐use, morphological, architectural, and social data are also needed, and those are being gathered using different approaches. The second is linked to the necessity for producing information directly connected to their effects on society. This requires a strong multidisciplinary approach, and nowadays impact studies are not limited to one dimension but instead cover multiple dimensions. The third is to transfer all this information to city practitioners, so that urban climate features are considered, among many other aspects, in city management. For urban planning, cartographic tools have been introduced to include urban climate diagnosis as well as recommendations for future urbanization. Abstract : Cities modify their local climate, and at the same time they suffer from the local impacts of climate change. This perspective article discusses the progress and obstacles in three active research areas in urban climate research that contribute to increasing the capability of researchers for transferring local climate knowledge to urban planners.